The usage of fintech applications that implicating coffee shop employee performance during the Covid-19 pandemic - Vera Sylvia Saragi Sitio (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Since the Dutch era, Indonesian people have developed the habit of drinking coffee. This habit has become part of the daily lives of Indonesian people, especially adults, and is now in demand among young people. From 2016 to 2019, record coffee consumption in Indonesia increased. This research was conducted from February 2020 to October 2021, with a sample of 100 respondents and a population of 195 respondents, and the study was conducted in East Jakarta culinary coffee shops versus SMEs. This study used live samples from the general population. From the point of view of the problem, the results of the study indicate that the perception of benefits has a direct positive and significant effect on performance. Perceived benefits have a positive and significant direct effect on user attitudes. Perception of comfort has a direct positive and significant effect on employee performance. Perception of convenience has a positive and significant direct effect on user attitudes. User attitudes have a positive and significant effect on employee performance. Perceived benefits have a positive and significant indirect effect on employee performance through user attitudes as an intervening variable. user as an intervening variable.